Ownership and utilisation of insecticide-treated mosquito nets among caregivers of under-five children and pregnant women in a rural community in Southwest Nigeria (2014)
Introduction. Malaria still constitutes a serious public health problem in Nigeria despite control efforts. The use of Insecticide Treated Net (ITN) has been proven to be an effective preventive modality in the control of malaria but its utilisation has been shown to be low. This study assessed the ownership and utilization of ITN in Igbo-Ora, a rural community in Ibarapa Central Local Government Area (LGA) of Oyo State, Southwest Nigeria. Methods. A descriptive cross-sectional survey among female caregivers of under-five children and pregnant women was conducted using semi-structured interviewer-administered questionnaire. Data were analyzed using SPSS version 16. Results. Among 631 respondents that participated, 84.9% were caregivers of under-five children. Mean age was 27.7 ± 6.3 years with 53.4% between 20-29 age group. Majority, 91.1% had at least primary education, 60.2% were traders and 69.7% were married. Most respondents, 71.8% had at least one type of mosquito nets. Among those that had, 85.4% had window/door net, 25.2% untreated mosquito net while only 15.5% had ITN. Overall, 11.1% of the respondents had ITN among which 78.6% had ever slept under an ITN. Among those that had ever slept under an ITN, slightly less than half, 49.1% slept under an ITN the previous night. Less educated respondents were five times more likely to use ITN (95% CI = 1.24-21.28). Conclusions. This study revealed very low ownership and utilization of ITNs. There is need to improve on the knowledge of community members of the relevance of ownership and utilisation of ITN in malaria prevention.